BUDGET USE AND PERFORMANCE OF MANUFACTURING SMALL AND MEDIUM ENTERPRISES (SMEs) IN LAGOS STATE, NIGERIA - Mubaraq Sanni; Oladipo Oluwafolakemi Fasesin (Malete Journal of Accounting and Finance)
The absence of budgets in the operations of SMEs often leads to their poor performance. SMEs ought to maintain proper budget, the lack of which may lead the businesses to remain small, stagnant and even close down in some cases. Consequently, this study seeks to examine the impact of budget use on the performance of SMEs. To achieve this main objective, specific objectives were developed with respect to: investigate the extent to which diagnostic budget use influences performance of manufacturing SMEs and examine the effect of interactive budget use on performance. The study employed cross-sectional research design to address empirical questions developed for the study. The population of the study was 46,652 managers (Managing Director, Account Manager, Human Resources Manager and Production/operation Manager) of manufacturing SMEs operating in Lagos State out of which 397 were randomly selected. The primary data were sourced from field survey through the administration of questionnaire. Data were sourced through a structured questionnaire from the selected 397 managers. Analysis was based on both descriptive and inferential techniques.  The descriptive analysis was based on techniques such as graphs and tables, while the inferential analysis was done by PLS-SEM techniques to test all the hypotheses. However, the results of the analysis reveal that both diagnostic and interactive budget use have a positive significant relationship with performance of Manufacturing SMEs in Lagos State at (β = 0.148, t = 1.75, p < 0.10 ) at 1%  level of significant and (β = 0.199, t = 2.75, p < 0.01) respectively. However, the use of budget diagnostically and interactively goes a long way to influence the performance of manufacturing SMEs in Lagos State. Consequently, the study recommends that manufacturing SMEs in Lagos State should have budgets to provide motivation and direction for managers to achieve their organizational goals and to contribute to a significant increase in managers’ organizational commitment due to greater flexibility regarding dialogue and respect for subordinates’ contribution.